K.D. Ushinsky as a teacher and mentor of Russian national pedagogy (to the 200th anniversary of his birth) - Lyubov’ A. Kochemasova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Considering the analysis of the scientific research, the author turns to revealing and understanding the pedagogical heritage of the outstanding teacher and scientist Konstantin Dmitrievich Ushinsky in the field of scientific knowledge. The paper focuses on the conceptual ideas of K.D. Ushinsky, which present the main provisions of the education and upbringing of the younger generation, the stages of professional training of the future teacher, the popular image of the teacher. The importance of the teaching profession for modern society is emphasized. The author pays special attention to the popularization of the teaching profession, the recognition of the special status of teaching staff, including mentoring, which is of particular importance in the Year of the Teacher and Mentor. The practical significance of the study is in the integration of pedagogical science and practice in the context of the challenges of the 21st century as a construct for the implementation of modern educational practices in the innovative activities of a teacher, tutor, mentor, facilitator by organizing and holding the International Competition for Research and Creative Works of Students In the World of Wise Thoughts K.D. Ushinsky. The presented results of the study update the pedagogical heritage of K.D. Ushinsky in modern pedagogical science and practice and can be used as a tool to attract students to the teaching profession.